Still have math questions?

Ask our expert tutors
Algebra
Question

(a) Differentiate \(y = ( x ^ { 2 } + 1 ) ^ { 5 }...

(a) Differentiate \(y = ( x ^ { 2 } + 1 ) ^ { 5 }\) , using the chain rule. Then use the product rule to differentiate \(y = x ( x ^ { 2 } + 1 ) ^ { 5 }\) .

(b) Differentiate \(y = ( 1 - x ^ { 2 } ) ^ { 4 }\) . Hence differentiate \(y = 2 x ^ { 3 } ( 1 - x ^ { 2 } ) ^ { 4 }\) .

(c) Differentiate \(y = ( x ^ { 2 } + x + 1 ) ^ { 3 }\) , then differentiate \(y = - 2 ( x ^ { 2 } + x + 1 ) ^ { 3 } x\) .

(d) Similarly, differentiate \(y = x ( 4 - 9 x ^ { 4 } ) ^ { 4 }\) .

Answer

\(\left. \begin{array} { l } { \text { 11(a) } 10 x ( x ^ { 2 } + 1 ) ^ { 4 } , ( x ^ { 2 } + 1 ) ^ { 4 } ( 11 x ^ { 2 } + 1 ) } \\ { \text { (b) } - 8 x ( 1 - x ^ { 2 } ) ^ { 3 } , 2 x ^ { 2 } ( 1 - x ^ { 2 } ) ^ { 3 } ( 3 - 11 x ^ { 2 } ) } \\ { \text { (c) } 3 ( 2 x + 1 ) ( x ^ { 2 } + x + 1 ) ^ { 2 } } \\ { - 2 ( x ^ { 2 } + x + 1 ) ^ { 2 } ( 7 x ^ { 2 } + 4 x + 1 ) } \\ { \text { (d) } ( 4 - 9 x ^ { 4 } ) ^ { 3 } ( 4 - 45 x ^ { 4 } ) } \end{array} \right.\)

Solution
View full explanation on CameraMath App.